2004
DOI: 10.1021/ie0400797
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic and Mass-Transfer Characteristics in Organic Liquid Mixtures in a Large-Scale Bubble Column Reactor for the Toluene Oxidation Process

Abstract: The gas holdup ( G ), Sauter mean bubble diameter (d S ), and bubble size distribution, as well as the volumetric mass-transfer coefficient (k L a), gas-liquid interfacial area (a), and mass-transfer coefficient (k L ), of N 2 and air were measured in a large-scale (0.316-m inside diameter, 2.8-m height) bubble column reactor (BCR) in toluene and its mixtures (toluene-benzoic acidbenzaldehyde) under a wide range of pressure (0.2-0.8 MPa) and superficial gas velocities (0.06-0.14 m/s). The k L a data were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 66 publications
3
30
0
Order By: Relevance
“…Some researchers found k L to be independent of U G [31][32][33][34]. Gopal and Sharma [35] found k L to decrease slightly with U G [12] while Lemoine et al [35] and Mena et al [36] found k L to increase with U G . Han and Al-Dahhan [19] found that k L increases with U G at low U G range but the increase in k L is not significant at high U G range.…”
Section: Effect Of Distributorsmentioning
confidence: 99%
“…Some researchers found k L to be independent of U G [31][32][33][34]. Gopal and Sharma [35] found k L to decrease slightly with U G [12] while Lemoine et al [35] and Mena et al [36] found k L to increase with U G . Han and Al-Dahhan [19] found that k L increases with U G at low U G range but the increase in k L is not significant at high U G range.…”
Section: Effect Of Distributorsmentioning
confidence: 99%
“…Froude number = U G /(gd) 1 dense phase (small gas bubble phase) G gas phase L liquid phase P solid particle SL slurry trans transition from homogeneous to heterogeneous…”
Section: Bomentioning
confidence: 99%
“…(1) to predict the corresponding total gas holdup. It should be emphasized that BCRs and SBCRs operating in the churn-turbulent flow regime, small and large gas bubbles were reported to coexist [1,15,19,28]; Eq. (1) is valid for predicting the total holdup of all the gas bubbles present.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] This verdict of the pressure effect on the k l values was corroborated by Lemoine. [44] The apparent decrease of k l is attributed to the change in bubble dynamics and hydrodynamics at 0.4 MPa. [45] At high pressure, smaller bubble sizes have lower slip velocity.…”
Section: Effect Of Operating Pressure and Gas Velocity On Mass Transfmentioning
confidence: 95%